Nonstoichiometric Oxides as Low-Cost and Highly-Efficient Oxygen Reduction/Evolution Catalysts for Low-Temperature Electrochemical Devices - Chen, D.; Chen, C.; Baiyee, Z.; Shao, Zongping; Ciucci, F. (American Chemical Society, 2015)
The recent advances in the development of nonstoichiometric oxides, ranging from simple oxide, perovskite, layered perovskite, and pyrochlore, for oxygen reduction Reaction (ORR) and oxygen evolution reaction (OER) in metal-air batteries (MABs) and low-temperature fuel cells (LTFCs) are reviewed. These catalysts are characterized to be low cost and earth-abundant, as well as possess relatively high activity and stability under operation conditions. It is expected that these catalysts will be essential to the future development of multiple technologies. It is expected that the development of nonstoichiometric oxides, with the mutual development of system components, will lead to highly stable and efficient MABs and LTFCs in practical applications in the near future. The electrochemical strain microscopy technique may provide a direct visualization of the ORR/OER activation process on the scale of several nanometers and provide nanoscale understanding into local kinetics. An efficient approach to discover new materials with high intrinsic activities is to tune the electronic structure of existing materials.